Evaluation of intravenous iron sucrose therapy for management of moderate to severe anaemia in pregnancy - Nimbalkar, Pankajkumar B.; Patel, Jaldhara N.; Thakor, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Iron deficiency anaemia (IDA) is the most common nutritional deficiency in pregnancy and major contributory factor to maternal morbidity and mortality. Objective of present study was to evaluate the response and effectof parenteral iron sucrose complex therapy in iron deficiency anemia in pregnancy. Methods: A prospective observational study was conducted at GMERS Medical College, Dharpur-Patan over a period extending from September 2014 to August 2017. A total of 150 Antenatal women, between 26-32 weeks of pregnancy with hemoglobin between 5-9 gm% were selected for study by purposive sampling. They were given intravenous iron sucrose complex in a dose of 200 mg (2 ampules of 5 ml each) in 100 ml normal saline over a period of 15-20 minutes, on alternate day. Repeat CBC was done after a period of 6 weeks. Results: Age range of the patients was 20 to 34 years. Out of total 150 women, 72 women (48%) were in age group of 20-24 years. 64.6% women had 27-29 weeks of pregnancy. 58 (38.6%) women had <8 gm% of Hb before treatment and 108 (72%) women achieved Hb of 10 gm% after treatment. The mean haemoglobin raised from 7.9±0.92 gm% to 10.3±0.83 gm% (P<0.001) after six weeks of therapy. There was significant rise in MCV levels (from 67.7±5.1 fl to 78.9±6.4fl) (P<0.001). Major side effects or anaphylactic reactions were occurred in none of the women during study period. 93.3% of patients, treated for anemia were delivered at full term, either vaginally (67.3%) or by LSCS (26%). Most of the delivered babies (80%), had birth weight of more than 2.5 kgs. Conclusions: Parentral iron therapy was effective in increasing haemoglobin and other haematological parameters in pregnant women with moderate to severe anaemia.